Investigating Sex Bias in the AQ-10: A Replication Study. (December 2019) - Murray, Aja Louise; Booth, Tom; Auyeung, Bonnie; McKenzie, Karen; Kuenssberg, Renate
There are concerns that females with autism spectrum disorders (ASD) may be underidentified because of factors such as better camouflaging and poorer recognition of the signs of ASD in females. One stage at which females may be underidentified is during screening. In this study, we, therefore, evaluated whether the autism spectrum quotient (AQ-10), a brief recommended screening instrument for ASD in adults suspected of having ASD, showed any evidence of underestimating symptoms in females. Our results broadly replicate those of an earlier study in finding no strong evidence that the AQ-10 is biased against females. However, to achieve better performance in females, we suggest that one item be replaced with an item measuring more "female" manifestations of ASD.